Математичне моделювання індукованого нейтроном ділення ядра 237Np - Oprea, C.; Ahmad, M.A.; Baker, J.H.; Oprea, A.I. (Publishing house "Academperiodika", 2022)
Recent progress of applied and fundamental researches in nuclear physics necessitates new neutron sources with highly improved intensity. For a few years at JINR (Dubna) the development of new neutron facilities that will replace the IBR-2 neutron pulsed research reactor, which will finish its activities in 2032, is carried on. Some projects use the fission process induced by neutrons in neptunium-based fuels. In the present research, we will study the neutron-induced fission of 237Np nucleus. The cross-section, mass distribution, yields of isotopes of interest, average number of emitted prompt neutrons, neutron fission spectra, and other parameters are obtained. The mathematical modeling is done partially by using the theoretical models implemented in Talys software (TALYS-1.2) and by computer codes realized by the authors. The presented results are compared with the available data and are of interest in the JINR projects for the design of new neutron facilities destined for researches.